Effect of indole-3-acetic acid on surface properties of the wheat plastid lipids - Filek, Maria (Journal of plant physiology, 2005)
Surface parameters of polar lipids extracted from winter wheat plastids were investigated by the Langmuir and X-ray differentiation scattering methods. Highly purified plastids were isolated from non-embryogenic (NE) and embryogenic (E) calli initiated from inflorescences. NE plastids contained more monogalactosyldiacylglycerol (MGDG) and digalactosyldiacylglycerol (DGDG) and less phospholipids (PL) fraction than E plastids. Moreover, in E calli, unsaturated fatty acids were detected in a higher proportion than in NE for both MGDG and DGDG. No significant differences in fatty acids saturation of PL between NE and E objects were detected. Aqueous surface monolayers were prepared from separate lipids and from mixtures of glycolipids and PL. In the case of MGDG, isotherms showed specific shoulders, contrary to continuous isotherms obtained for other investigated lipids. On the base of pi-A isotherms, the surface parameters: limiting area (A(lim)) and collapse pressure (pi(coll)) were calculated. Indole-3-acetic acid (IAA) increased the A(lim) of all separated lipids about 4-10 angstrom2/mol. However, for NE lipid mixture, the effect of IAA was much smaller (about 2 angstroms2/mol) than for other objects (usually about 5 angstroms2/mol). X-ray experiments for liposomes, obtained from mixtures of glycolipids and PL of NE and E plastids, showed continuous scattering curves with maxima characteristic for lipid bilayer membranes. Calculations of distance distribution functions indicated that bilayer thickness was 41 and 38 angstroms for NE and E, respectively. IAA influence on membrane structures was detected especially in E liposomes and increased the distance between head groups by about 2 angstroms. It is suggested that changes occur during embryogenesis in specific structure of plastid membranes determined also the formation of domains, similar to that suggested for plasmalemma (Plant Sci. 165 (2003) 265). IAA treatment influenced the membrane structure, especially E plastids increasing distances between polar groups